Prediction of acid production potential of self-combusted coal mining wastes from Douro Coalfield (Portugal) with integration of mineralogical and chemical data - Celebi, Emin Ender; Ribeiro, Joana (Elsevier, 2023)
The prediction of acid production potential (APP) of coal waste piles that underwent self-combustion was investigated by integrating mineralogical and chemical data to secure a sustainable environment. Burned and unburned material from three waste piles in Douro Coalfield (Portugal) were studied to understand the effect of self-combustion on APP. For this purpose, mineralogical analysis, paste pH, infrared spectroscopy, acid ammonium oxalate leaching, and nitric acid leaching were performed to determine the most reliable APP scores, while British Columbia Research Initial test was carried out for the neutralization potential (NP) determination. The major acid producers were pyrite and jarosite, while the neutralizers were calcite, aragonite, azurite, siderite and hydrotalcite as rare accessory minerals. Hence, APP scores were determined in terms of the calculation factors of pyrite and jarosite. A thermal transformation from jarosite to hematite was detected due to self-combustion. The presence of hematite and mullite minerals in extremely burned wastes is in the foreground. After obtaining APP and NP, net acid production potential (NAPP) scores were calculated and subsequently interpreted with net acid generation (NAG) test results. The NAPP scores between 0.7 and 24.1 kg CaCO3/t were obtained, while the negligible level of NP scores was between 0.1 and 1.6 kg CaCO3/t. According to six different acid mine drainage (AMD) screening criterion, most of samples were detected as potentially acid forming. The interpretation of non-acid forming was not concluded for any wastes. Consequently, the piles are moderately prone to form AMD, and the NAPP in extremely burned zone of the piles is lower than the zones of partially burned and unburned due to the loss of sulfide and scarcity of acid sulfates.
Keywords: Coal mining waste; Self-combustion; Mineralogical alteration; Acid mine drainage